Using well log data to predict rock compressibility and elasticity in Zubair formation/ southern of Iraq - Nather, Hiba Alaa Al-Deeen; Abdul-Majeed, Rwaida Kaiser; F. Mukhtar, Yasir M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The mechanical characteristics of rocks such as elasticity (Young’s modulus, Poisson’s ratio, and unconfined compressive strength) play an essential in sand production analysis, well design, and borehole stability assessment. In this study, the mechanical characteristics of rocks were indirectly estimated using gamma ray, density, and acoustic (compressional and shear) log data from well RU-X in the Rumaila oil field, specifically for the Zubair Formation. These estimated properties were compared to direct measurements obtained from triaxial and uniaxial mechanical tests conducted on well RU-X. The results showed a significant similarity between the indirect estimates and the direct measurements, indicating their reliability for sand production analysis and their valuable contribution to constructing the geomechanical model. Moreover, the static profile of Poisson’s ratio was validated using laboratory core test results, demonstrating reasonable agreement. The validation process involved comparing laboratory-derived measurements with actual field measurements in the Zubair Formation. The higher Poisson’s ratio observed in the shale was attributed to the slower propagation of acoustic waves, resulting in a good matching with an R2 value of 0.77. On the other hand, the lower Young’s modulus in the shaly formations indicated lower resistance to deformation, with a comparative ratio of R²=0.96. Static measurements, which consider various influencing factors, provide a more realistic representation of rock behavior under different conditions. Regarding unconfined compressive strength, the comparative ratio was R²=0.83.